Flux of the professional standards: Objectivity, Advocacy journalism and Paradigm Repair - Kulic, Milica (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
Looking at media content, especially since the beginning of the war in Ukraine in 2022 and the subsequent conflicts, it is repeatedly confirmed that basic journalistic principles are entangled in political and economic agendas. Media-dictated agendas have become the framework within which thinking is constrained. Public opinions are confined within existing agendas, further restricted by new media iron curtain. The media, captured not only by individual political and economic interests of the government or owners but also by the necessary global worldview to which the government belongs, are restrained. Journalists seem to be expected not to be objective but engaged, fueling ideological frameworks and refraining from questioning their own policies, thus reinforcing the fortress of ideological extremism where media and their owners sit. Therefore, this theoretical work will examine changes in the journalistic profession by questioning objectivity in the context of a paradigm repair. It will attempt to establish whether the journalistic profession requires new definitions or can exist within its traditional professional framework. Additionally, it will try to determine whether the process of media capture is a legitimization of the existing state or a propaganda context of the era that professional journalism can address.